2017
DOI: 10.1016/j.marpolbul.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Large microplastic particles in sediments of tributaries of the River Thames, UK – Abundance, sources and methods for effective quantification

Abstract: Lahive, Elma. 2017. Large microplastic particles in sediments of tributaries of the River Thames, UK -abundance, sources and methods for effective quantification.Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner.  Many fragments derived from road marking paints -a previously undescribed source. Efficient methods develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
295
2
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 760 publications
(326 citation statements)
references
References 51 publications
18
295
2
11
Order By: Relevance
“…In addition, the site is much closer to sewage and stormwater outfall drains, which we found to be sources of plastic pollution in previous work (Willis et al, 2017). This result is similar to those found in other studies, which found higher numbers of plastics at sites closer to storm drain outfalls (Duckett and Repaci, 2015;Horton et al, 2017). Most microplastics observed were fibers (87%).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the site is much closer to sewage and stormwater outfall drains, which we found to be sources of plastic pollution in previous work (Willis et al, 2017). This result is similar to those found in other studies, which found higher numbers of plastics at sites closer to storm drain outfalls (Duckett and Repaci, 2015;Horton et al, 2017). Most microplastics observed were fibers (87%).…”
Section: Discussionsupporting
confidence: 90%
“…However, although 376 particle numbers are regularly found to be high near urban areas, this is not the only factor influencing 377 presence of microplastic particles. For example, Horton et al (2016), in addition to finding high 378 numbers of particles downstream of urban discharge points, also found particles in rural areas where 379 few human-associated inputs would be expected. 380…”
mentioning
confidence: 99%
“…Phosphorus and nitrogen sources and dynamics in the River Thames (Neal et al, 2010a;Neal et al, 2000c) and its tributaries 15 (Bowes et al, 2012c;Jarvie et al, 2006;Jarvie et al, 2002b;Neal et al, 2000a;Neal et al, 2004;Neal et al, 2006), and how nutrients interact with river ecology (House et al, 2001;Jarvie et al, 2002a;Williams et al, 2000) have been intensively studied in recent decades. These studies were based on one to two year periods of weekly monitoring by the Centre for Ecology & Hydrology (CEH), based at a small number of individual study sites, carried out between 1997 and 2008.…”
mentioning
confidence: 99%
“…The resulting data sets 10 have been extensively used as a modelling resource (Bussi et al, 2017;Bussi et al, 2016;Hutchins et al, 2016;Whitehead et al, 2015). Other studies have used the Thames Initiative monitoring sites as a framework for investigations of organic pollutants (Nakada et al, 2017;Singer et al, 2014), heavy metals (Turner et al, 2014), emerging contaminants (Horton et al, 2017), and antimicrobial resistance (Amos et al, 2015).…”
mentioning
confidence: 99%